Effect of thermomechanical treatment on microstructure of guar gum/acid milk gels. (February 2016) - Rohart, Anne; Michon, Camille
Abstract: The influence of thermal and shear conditions on the final microstructure and rheological properties of guar gum/acid milk gels was investigated. In an immiscible guar gum/milk mixture, gelation can kinetically trap the sedimenting protein-rich droplets. In order to modify the phase separation and gelation kinetics, acidification procedure, shear and thermal histories were modified. The properties of the set and stirred mixed gels were then discussed in light of the processing conditions applied and the relative phase separation and gelation times. Application of various thermal stages showed an increase in the sediment layer and a modification of the morphology of the micro-gels when delaying both the phase separation and gelation mechanisms. Moreover, a substantial reduction of the phase separation could be obtained by applying a continuous shear until different stages of acidification. The results demonstrated that the size and shape of the micro-gels depended not only on the time interval between phase separation and gelation, but also on thermal and shearing conditions. Highlights: Design of a technological pathway using GDL and thermomechanical histories. In-depth characterization of mixed acid milk gels properties was performed. Relative phase separation and gelation kinetics were affected by thermal and shear conditions. Processing conditions were of critical importance for the acid milk gels properties.